1999
DOI: 10.1103/physreva.60.r2622
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cryptography using femtosecond-pulsed parametric down-conversion

Abstract: A new scheme for quantum cryptography, based on a distributed polarization quantum intensity interferometer, is presented. Two-photon entangled states generated via the optical nonlinear process of type-II phasematched spontaneous parametric down-conversion are used to securely distribute secret cryptographic keys. The high contrast and stability of the quantum interference pattern obtained by using this design renders it superior to the best existing single-photon polarization technique. In addition, the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
57
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 18 publications
1
57
0
Order By: Relevance
“…Scientists are currently using one of two photon sources for practical QKD, faint lasers [5,6,7,8,9,10] or spontaneous parametric down-conversion to generate entangled photon states (SPDC) [11,12,13,14,15].…”
mentioning
confidence: 99%
“…Scientists are currently using one of two photon sources for practical QKD, faint lasers [5,6,7,8,9,10] or spontaneous parametric down-conversion to generate entangled photon states (SPDC) [11,12,13,14,15].…”
mentioning
confidence: 99%
“…Unfortunately, femtosecond pulse pumped SPDC shows relatively poor quantum interference visibilities (Keller and Rubin, 1997). The following methods are used to increase the quantum interference visibility: (i) a thin nonlinear crystal (Sergienko et al, 1999), (ii) narrow-band spectral filters in front of detectors, as shown above (Grice and Walmsley, 1997;Grice et al, 1998;Di Giuseppe et al, 1997), or (iii) an interferometric technique (Branning et al, 1999(Branning et al, , 2000 without spectral and amplitude post-selection, which was making the spectral wave function of the two photons much more symmetric. 25 The first two methods reduce the intensity of the entangled photon pairs significantly and cannot achieve perfect overlap of the two-photon amplitudes.…”
Section: New Methodsmentioning
confidence: 99%
“…This confirms Eq. (8). In other words, we have successfully prepared polarization Bell states from femtosecond pulsepumped SPDC without amplitude and spectral postselection.…”
mentioning
confidence: 99%
“…One has to utilize special experimental schemes to achieve complete overlap of the twophoton amplitudes. Traditionally, the following methods were used to restore the quantum interference visibility in femtosecond pulse pumped type-II SPDC: (i) use a thin nonlinear crystal (≈ 100µm) [8] or (ii) use narrow-band spectral filters in front of detectors [6,7]. Both methods, however, reduce the available flux of the entangled photon pair significantly [9] and cannot achieve complete overlap of the wave-functions in principle [6].…”
mentioning
confidence: 99%